Effect of a Family Participation Promotion Program on Family Practice of Dental Care Among Preschool Children - Pichairattanawong, Pilaiwan; Tuanrat, Wilawan; Aungwattana, Sivaporn (Nursing Journal CMU, 2023)
Encouraging parental participation in dental health for preschool children will aid in the prevention of tooth decay problems. This quasi-experimental, two-group, pretest-posttest design aimed to investigate the effect of a family participation promotion program on families’ dental care practice for their preschool children. The participants, 36 parents of preschool children in a child development center, were assigned by simple random sampling to one of two groups of 18. One group received the program, and one did not. The sample group was selected under purposive sampling criteria. The research tools consisted of the family participation enhancement program devised by the researcher based on community participation and lasting for 8 weeks. It consisted of instructional plans, a family participation promotion manual, slide-show media, video instructors, a family participation promotion kit, and LINE apps. The data collecting instrument consisted of a questionnaire on family practices regarding the dental health care of their preschool children with a Pearson’s product moment correlation coefficient of .94. Data were analyzed using descriptive statistics, independent t-test, and paired t-test. The results indicated that the group receiving the program had a higher average score for family practice in the dental health care of their preschool children after receiving the program (Mean = 23.17, SD = 0.92) than before (Mean = 17.94, SD = 2.94) with a statistically significant difference (t = -9.085, p < .001). After receiving the program, the group who had received the program had a higher average score for family practice in the dental health care of their preschool children (Mean = 23.17, SD = 0.92) than the group not receiving the program (Mean = 19.11, SD = 3.35) with a statistically significant difference (t = 4.940, p < .001). The results from this study show that the family participation promotion program on family practice of dental care among preschool children can be used to promote the dental health care of preschool children.